Dreams, Visions and the African Melodrama: A Commentary on the Interface between Cinematography and Pentecostal Epistemology - Droll, Anna (PentecoStudies, 2022)
Pentecostal films in Africa have gained the attention of humanitarians concerned with the societal effects of witchcraft preoccupation. As well, they are of interest to anthropologists examining Spirit movements. Humanitarians address the ethical problem perceived in the Pentecostal melodrama and its narratives, while anthropologists and proponents of religious studies focus on the social and technological aspects of Pentecostal filmmaking and the discourses produced by these films within the religious landscape. This essay brings another avenue of exploration. It supplements the anthropological approach by exploring the Pentecostal narratives found at the interface of cinematography and Pentecostal epistemology for their theological substance. It is argued here that the Pentecostal melodrama is not only unique for how it serves as an epistemological technique for "piercing the veil" to expose the true state of things. It is also unique for how its narratives, themselves, are often products of a similar piercing, that is, of the dream or vision experience which visioners experience as the phenomenon of piercing the veil beyond the mundane to the noumenal. Referencing data drawn from recent dream research, this article explores the interpretive processes inherent to Pentecostal mediation of the seen and unseen, the role of prayer in that process and the suggestion that cinematography embodies the liturgical expression of a distinct Pentecostal epistemology.